208 Assessment of The Impact Of COVID-19 On the Management of Patients with Neck of Femur Fractures in A Major Trauma Center In Wales. (4th May 2021) - Solari, F; Ansar, Z
Abstract: Introduction: Neck of femur (NOF) fractures form a significant proportion of trauma. Especially since they do not benefit from COVID-19 social isolation policies. Surgery and hospital admissions present risks to patients during the COVID-19 pandemic. Method: Retrospective analysis of all NOF fractures from 24/3/20 to 26/6/20 in Morriston Hospital. Directly compared with 2019, allowing assessment of COVID-19's impact. Results: 179 NOF fractures were admitted, 158 had an operation. Increased from 127 patients in 2019. Average time to surgery increased from 39 to 67 hours. There were operation delays for 98 patients, and non-operative treatment increased from 2 to 21 patients. Prompt orthogeriatric reviews completed in 80.4% patients in 2020, up from 72.5%. Prompt physiotherapy review increased from 66.9% to 74.6%. Mortality remained similar at 8.6% (2019) and 8.5% (2020). Average length of stay reduced; 17.4 to 11 days in 2020. Conclusions: 2020 saw increased waits for operations. There was reduction in length of stay and improved promptness of orthogeriatric and physiotherapy reviews. Increased non-operative treatment in 2020, reflecting decisions about risks and benefits of surgery in the pandemic. Mortality remained stable. This department improved some aspects of care, potentially due to pressures of COVID-19 heightening awareness of patient's needs.